Meningkatkan Literasi Kesehatan Holistik di Kalangan Diaspora Indonesia di Malaysia Menggunakan Bumbu Tradisional Indonesia - Suaebah, Evi; Primary Putri, Nugrahani; Munasir; Anggaryani, Mita; Sunarti, Titin; Hari Kusumawati, Diah; Satriawan, Muhammad; Saputra, Oka; Apridiana Lestari, Nurita; Fadhilah, Nisa’ul; Khoiro, Muhimmatul (Journal of Dedication in Community, 2025)
This community service program aimed to improve knowledge, perceptions, and behaviors of the Indonesian diaspora at the Sungai Mulia Learning Studio (SBSM) in Kuala Lumpur, Malaysia, regarding the use of traditional spices for health. The program involved counseling, demonstrations, and completion of an evaluation questionnaire using a Likert scale and open-ended questions. Twenty-three participants took part in the activities and evaluations. The results showed high levels of knowledge and positive perceptions, especially in participants’ belief in the health benefits of traditional spices and their understanding of the functions of basic spices such as ginger and turmeric, commonly used as traditional medicines. Although some participants still chose modern medicine as their main option, they demonstrated a positive attitude toward herbal remedies. Behavioral analysis indicated a strong tendency to prepare, consume, and seek information about spices after attending the program. Qualitative findings supported these results; most participants stated that the activities were beneficial, broadened their insight, and encouraged habit changes toward greater use of herbal medicine. All participants also expressed willingness to join follow-up programs. Overall, this program effectively improved spice-based health literacy and has the potential to be scaled up through more intensive practical sessions and provision of guidance materials.